TOPSIS method analysis for company financial performance ranking based on DER, ROA, AND PBV - Padang, Novi Natalia; Erlina, Erlina; Muda, Iskandar; Nasution, Abdillah Arif (Edelweiss Applied Science and Technology, 2024)
Energy resources are a crucial component of economic and social growth in Indonesia. Energy businesses are a significant part of the national economy, and their performance directly affects the stability of energy supply, economic stability, and the attainment of sustainable development objectives. application of the TOPSIS method (Order Preference Technique with Similarity to Ideal Solution) to initiate and rank the financial performance of energy companies in Indonesia. The main focus of this study is on three financial indicators: Debt to Equity Ratio (DER), Return on Assets (ROA), and Price to Book Value (PBV). The TOPSIS method offers a systematic and objective framework for decision making by normalizing data, assigning weights to each criterion, and calculating the distance from the ideal solution. The results show that this method can effectively rank companies based on their financial metrics, which can facilitate better strategic decision making in the energy sector. This study aims to contribute to the development of information technology-based decision support systems to improve energy resource management in Indonesia and drive sustainable economic growth. In this analysis, the MLBI company achieved the highest ranking with a closeness coefficient of 0.703569, outperforming other companies such as KEJU and AISA. This ranking can be used to guide strategic decisions, improve debt management, and increase stakeholder trust.